Protecting children from abuse and neglect in primary care - Bannon, Michael J., Dr; Carter, Yvonne, 1959-2009 (Oxford University Press, 2003)
"Protecting Children From Abuse and Neglect in Primary Care deals with child abuse and neglect as it presents itself in primary care. All health professionals, including those who work in primary care, have an important role to play in the child protection process. Inappropriate management of suspected instances of child abuse may result in serious implications for the child, family and involved professionals. Primary health care teams have specific and unmet training needs in this area and many general practitioners express anxiety regarding their involvement in child protection work. The overall aim of this book is to enable members of the primary health care team to fulfil their responsibilities in the protection of children from the threat of abuse or neglect. Readers are made aware of the skills required both to protect children and to subsequently maintain relationships with families. The contents have been extended to include child protection issues in our multi-cultural society along with comparison of different systems across Europe. The book is primarily aimed at GPs and their teams but social workers and health care managers will also benefit from its unique treatment of child protection issues in a primary care setting."--Jacket